Молекулярний аналіз тонких плівок різної природи на основі спектроскопії поверхневих плазмонів - Костюкевич, С.О.; Христосенко, Р.В.; Костюкевич, К.В.; Коптюх, А.А.; Суровцева, О.Р.; Крючин, А.А. (Реєстрація, зберігання і обробка даних, 2018)
Досліджено процеси формування та структуру тонких плівок халькогенідного склоподібного напівпровідника As₂S₃, полімеру поліаніліну (ПАНІ) та білка фібриногену (ФБ) на поверхні плівок благородних металів (Ag, Au) з використанням методики призмового збудження поверхневого плазмонного резонансу (ППР) у поєднанні з атомно-силовою мікроскопією. Оптичні параметри шарів As₂S₃ та ПАНІ визначено при підганянні експериментальних і розрахованих резонансних кривих ППР методом мінімізації цільової функції. Властивості плівок ФБ, що отримані з розчину білка у фосфатному буфері при різних концентраціях (9,3–300 muг/мл), вивчено на основі аналізу кінетичних ППР-кривих адсорбції ФБ і його DD- і E-фрагментів з наступним зондуванням моноклональними антитілами. Исследованы процессы формирования и структура тонких пленок халькогенидного стеклообразного полупроводника As₂S₃, полимера полианилина (ПАНИ) и белка фибриногена (ФБ) на поверхности пленок благородных металлов (Ag, Au) с использованием методики призменного возбуждения поверхностного плазмонного резонанса (ПИР) в сочетании с атомно-силовой микроскопией. Оптические параметры слоев As₂S₃ и ПАНИ определены при подгонке экспериментальных и рассчитанных резонансных кривых ППР методом минимизации целевой функции. Свойства пленок ФБ, полученных из раствора белка в фосфатном буфере при различных концентрациях (9,3-300 цг/мл), изучены на основе анализа кинетических ППР-кривых адсорбции ФБ и его DD- и E-фрагментов с последующим зондированием моноклональными антителами. Photodoping process in the thin film structures metal/chalcogenide vitreous semiconductor (Ag-As₂S₃), electro-polymerization mechanism of the polyaniline (PANI) films and formation mechanism of the fibrinogen (FB) molecular films on gold film surfaces were investigated by means of the surface plasmon resonance (SPR) technique based on prism excitation and mechanical scanning of incidence light angle in aggregate with atomic force microscopy (Nanoscope IIIa Dimension 3000).
Features of the FB molecular films formation, at the different concentration (9,3–300 mg/ml) of the protein in phosphate buffer (mm 7,4), were studied based on SPR kinetic curve, when the adsorption of three proteins, FB, its DD- and E-fragments and subsequent their adlayers interactions with monoclonal antibodies against different epitops in native molecules, that were going on the gold film surfaces. Displayed is the formation of the continuous film at the 73 Mg/ml concentration in buffer is visualized, during irreversible adsorption the alteration of the FB molecule structure in the sphere of its D-fragment take place, and the local self-assembling process leads to formation of the special molecular arrangement in biofilm, consist of three overlap FB molecules, where approximately 50 M of total adsorbed molecules which retain their biofunctional properties.